The effect of service quality and quality of savings products on customer satisfaction at islamic banks in Indonesia bekasi branch office 2 - Umi Kulsum; Risa Bhinekawati; Saprudin Saprudin (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
The purpose of this study was to find out whether there is an influence between service quality and the quality of savings products partially on customer satisfaction at Bank Syariah Indonesia. The second objective is to determine whether there is an effect between the quality of service and the quality of savings products simultaneously on customer satisfaction at Bank Syariah Indonesia. The results of the study indicate that there is an effect of service quality and the quality of savings products partially or simultaneously on customer satisfaction at Bank Syariah Indonesia. The quality of service in this study affects customer satisfaction and the quality of savings products does not affect customer satisfaction.